Visual Analysis of Coordinated Evaluation of Water Resources Utilization and Economic Development in China - WU Dan; XIANG Xiaoqian (Renmin Zhujiang)
Given the literature on the coordinated evaluation of water resources utilization and economic development in China from 1994 to 2020 in the core database of CNKI,the paper uses the visualization tool CiteSpace 5.7.R2 and the scientometrics method to analyze literature characteristics,as well as research focuses and their evolution,and delves into the evolution of the research on this field.The research reveals that according to the distribution of publication time and journals,the number of articles in this field shows an S-shaped curve,going through the starting,growing,and developing stages,and the research focuses are closely combined with national policy on water conservancy.In terms of the distribution of cooperation between universities and research institutions and the characteristics of cooperation among scholars,the phenomenon of extensive dispersion with localized concentrations is presented.The knowledge graphs of keyword networks demonstrate that the terms including “water resources”,“coordinated development”,“water resources carrying capacity”,“social economy”,“index system”,“industrial structure”,and “spatiotemporal coupling” have become popular in this field in the past decade.According to the strategy map of keywords,research themes represented by keywords such as “water footprint”,“urbanization”,“water and soil resources”,and “water environment carrying capacity” are developed into emerging research focuses.The time zone maps of keywords indicate that the application of the water-driven effect and its decoupling evaluation have become a new field of academic research.